THE ISSUE OF EDUCATIONAL PROCESSES IN JADID SCHOOLS - Akhrorov Ikhtiyar Donyorovich (Journals Park Publishing, 2022)
In this article, educational processes and methods of teaching secular sciences in the early modern schools of Turkestan are scientifically and theoretically analyzed based on important sources.
Keywords: New method, geometry, calculus, reading book, recitation book